Diagnostic dilemma in a case of neonatal cardiac tumor - The importance of histopathology and mutation analysis in clinical practice - Syamal Sardar; Rakesh Dey; Suchandra Mukherjee; Somnath Pal (Wolters Kluwer Medknow Publications, 2023)
Fetal or neonatal cardiac tumors are rarely encountered in neonatal practice. Moreover, these can be the earliest manifestation of underlying systemic conditions, such as tuberous sclerosis. Cardiac tumors are primarily diagnosed by characteristic findings in transthoracic echocardiography. However, these findings are not absolute, and histopathology remains the gold standard in diagnosing cardiac tumors. Sometimes, doubtful imaging findings can delay the diagnosis and initiation of definitive management. We describe a case of fetal and neonatal cardiac tumor where histopathology served as a benchmark in making a diagnosis and helped in identifying the underlying systemic disease.